Effect of organic manures and zinc in enhancing the growth, yield and quality of carrot (Daucus carota L.) (Indian Journal of Arid Horticulture, 2025)
The application of poultry manure applied at 4 t/ ha significantly improved plant height, number of leaves per plant, leaf area, root weight, root diameter, root length, root yield, as well as nitrogen and zinc content in carrot roots. Similarly, foliar application of ZnSO4 @ 0.75% significantly improved the growth attributes, yield parameters, and quality characteristics such as nitrogen and zinc content in carrot roots. The combined application of poultry manure @ 4 t/ ha with ZnSO4 @ 0.75% proved to be the most effective in improving growth, yield and quality of carrot.
Keywords: Organic manure; poultry manure; zinc sulphate and carrot